Calgizzarin (S100A11): a novel inflammatory mediator associated with disease activity of rheumatoid arthritis - Lucie Andrés Cerezo; Barbora Šumová; Klára Prajzlerová; David Veigl; Dres Damgaard; Claus Henrik Nielsen; Karel Pavelka; Jiří Vencovský; Ladislav Šenolt (Arthritis Research & Therapy, 2017)
Abstract Background Calgizzarin (S100A11) is a member of the S100 protein family that acts in different tumors by regulating a number of biologic functions. Recent data suggest its association with low-grade inflammation in osteoarthritis (OA). The aim of our study is to compare S100A11 expression in the synovial tissues, synovial fluid and serum of patients with rheumatoid arthritis (RA) and osteoarthritis (OA) and to characterize the potential association between S100A11 and disease activity. Methods S100A11 protein expression was detected in synovial tissue from patients with RA (n = 6) and patients with OA (n = 6) by immunohistochemistry and immunofluorescence. Serum and synovial fluid S100A11 levels were measured by ELISA in patients with RA (n = 40) and patients with OA (n = 34). Disease activity scores in 28 joints based on C-reactive protein (DAS28-CRP) were used to assess disease activity. Cytokine content in peripheral blood mononuclear cells (PBMCs), synovial fibroblasts (SFs) and synovial fluid was analysed by ELISA, western blotting or cytometric bead array. Results S100A11 expression was significantly up-regulated in the synovial lining and sublining layers (p < 0.01) and vessels (p < 0.05) of patients with RA compared to patients with OA, and was associated with fibroblasts and T cells. S100A11 was significantly increased in synovial fluid (p < 0.0001) but not in serum (p = 0.158) from patients with RA compared to patients with OA when adjusted for age and sex. Synovial fluid S100A11 correlated with DAS28 (r = 0.350, p = 0.027), serum CRP (r = 0.463, p = 0.003), synovial fluid leukocyte count (r = 0.677, p < 0.001), anti-cyclic citrullinated peptide antibodies (anti-CCP) (r = 0.424, p = 0.006) and IL-6 (r = 0.578, p = 0.002) and IL-8 (r = 0.740, p < 0.001) in synovial fluid from patients with RA. PBMCs and SFs isolated from patients with RA synthesized and spontaneously secreted higher levels of S100A11 in comparison with PBMCs and SFs from patients with OA (p = 0.011 and 0.03, respectively). S100A11 stimulated the production of the pro-inflammatory cytokine IL-6 by PBMCs (p < 0.05) and SFs (p < 0.01). Conclusions Our data provide the first evidence of S100A11 up-regulation and its association with inflammation and disease activity in patients with RA.